Literature Review of ISO 14001 Environmental Management System Benefits and Proposed Applications in the Defense Industries - Muktiono, Eka; Soediantono, Dwi (AGUSPATI Research Institute, 2022)
The purpose of this article is to explore the benefits of implementing the ISO 14001 Environmental Management System in various industries and provide suggestions for application to the defense industry. The method of writing this article is a literature review, which is a review by collecting, understanding, analyzing and then concluding as many as 30 international journal articles about the ISO 14001 Environmental Management System published from 2015 to 2021 regarding the application of the ISO 14001 Environmental Management System method in various industrial sectors and the defense industry. The analysis used is 30 journal article content analysis. The results of the literature review analysis state that the application of the ISO 14001 Environmental Management System method can improve the company's image, increase employee participation, reduce environmental pollution, increase market share and consumer demands, Can increase consumer confidence and provide a good image, Increase efficiency to be able to compete in the market globally, so as to gain profit so that the ISO 14001 Environmental Management System is recommended to be applied in the defense industry.